Public Health Education to Rural Teens - Han, Jing (My University, 2013)
The overall focus of this field experience was to communicate nutrition education content effectively to teens in rural Kansas while respecting cultural diversity; recognizing the needs and learning style of the targeted audience; learning program coordination and development, and demonstrating leadership, teamwork, communication skills and creativity in developing food culture and nutrition education resources. The field experience took place in Randolph, KS during the spring and fall semesters of 2012. To combine my interest in education and degree emphasis in human nutrition, I accepted the volunteer teaching position at Blue Valley high school to teach Chinese food culture and healthy eating in the science classes. The Chinese food culture classes were conducted first in order to minimize the differences in the language and culture background, to communicate effectively with the students, and increase the interests of the class. Secondly, the students received information on the benefits associated with eating breakfast, fruits and vegetables, and food safety to help them make healthier eating choices. In summary, I feel very positive about the experience. It provided the ideal combination of my nutritional knowledge and personal interests in culture education. As a presenter, I got a comprehensive multi-level experience by applying knowledge acquired throughout my education, increasing my understanding of the American educational system, learning under the supervision of a professional in the field, recognizing the needs and learning style of the targeted audience, and experiencing the various components of the Knowledge of Nutrition and Activity for Communities in Kansas (K.N.A.C.K.) youth curriculum. As an instructor, I helped students identify the benefits of different types of food, experience the Chinese food culture, and increased their understanding of nutrition to make healthier food choices. In essence, this field experience gave me an opportunity to take a theory and put it into practical application in a safe environment.
Keywords: Public Health; Rural Teens; Chinese Food Culture; Public Health (0573)